Dynamics of fiscal resilience: A comparative analysis of tax buoyancy in South and Southeast Asia - Wijaya, Suparna; Ghery, Syahra; Harits, Naufal Muhammad; Aulia, Clara; Hanifah, Hadijah; Ardana, I Putu Wisnu (Educoretax, 2025)
This research aims to explore, analyze, and compare tax buoyancy in South Asian and Southeast Asian countries through a comprehensive literature study approach. The secondary data used in this study were obtained from various reliable sources such as indexed academic journals, reports from international organizations (IMF, World Bank, ADB), and government policy documents. The analysis shows significant variations in tax buoyancy across countries, influenced by the complexity of tax systems, effectiveness of fiscal policies, levels of tax compliance, and macroeconomic conditions. Countries with more efficient tax administration systems, broad tax bases, and higher compliance levels exhibit greater tax buoyancy (>1), reflecting tax revenue capacity that is responsive to economic growth. Conversely, countries with less effective tax systems, narrow tax bases, and low compliance experience lower tax buoyancy (<1). This research reveals that income taxes and value-added taxes consistently show higher buoyancy compared to customs duties and excise taxes in both regions. These findings provide important policy implications for the development of more adaptive and effective fiscal policies in the region, particularly through comprehensive tax reforms, strengthening tax administration, broadening the tax base, and improving taxpayer compliance to support sustainable economic development.